Development of Abiraterone Acetate Nanocrystal Tablets to Enhance Oral Bioavailability: Formulation Optimization, Characterization, In Vitro Dissolution and Pharmacokinetic Evaluation - Yuanfen Liu; Yuqi Li; Pengcheng Xu; Yan Shen; Baoqiang Tang; Qiyue Wang (MDPI AG, 2022)
Abiraterone acetate is a prodrug of abiraterone used in combination with prednisone as a standard therapeutic strategy for hormone-resistant prostate cancer (mCRPC). Due to the poor solubility and permeability, the release and absorption of abiraterone acetate are low and reduce its bioavailability. In this project, abiraterone acetate tablets prepared using nanocrystal technology were developed to overcome the drawbacks of normal tablets by enhancing in vitro dissolution rate and oral bioavailability. The abiraterone acetate nanocrystal suspensions were prepared by top-down wet milling method using a planetary ball mill with the mixture of Poloxamer 407 and Poloxamer 188 as the optimized stabilizer at a ratio of 7:1. The optimized nanocrystals were freeze-dried and characterized using DLS, TEM, DSC, and XRD. The abiraterone acetate nanocrystal tablets significantly improve the in vitro dissolution rate of abiraterone acetate compared to raw materials. Although exhibiting a similar dissolution rate compared to the Zytiga® tablets, the nanocrystal tablets significantly improve the oral bioavailability with Cmax and AUC0-t being 3.51-fold and 2.80-fold higher, respectively, in the pharmacokinetic study. The present data indicate that nanocrystal is a promising strategy for improving the dissolution and bioavailability of abiraterone acetate.